Early education pilot for two year old children: evaluation - Smith, R; Purdon, S; Schneider, V; La Valle, I; Wollny, I; Owen, R; Bryson, C; Mathers, S; Sylva, K; Lloyd, E (Department for Children, Schools and Families, 2009)
This report provides the findings of the evaluation of the early education pilot for disadvantaged two year old children (the pilot). This study aimed to assess the impact of the pilot by looking at: how well the pilot was targeted, parents’ experiences of taking up a pilot place, the quality of the pilot settings, the impact on the children’s behaviour, and parents’ views and experiences of using a pilot place. The pilot provided free early years education to over 13,500 disadvantaged two year olds between 2006 and 2008. The main purpose of the pilot was to improve children’s social and cognitive outcomes, e.g. their social confidence and independence, and their verbal skills and reasoning ability. Additional aims were to have a positive impact on children’s parents and wider family e.g. on the relationship between parents and their children, or on parent’s emotional wellbeing. The funding offered these children 7.5 or in a small number of local authorities 12.5 hours of early years education per week for 38 weeks of the year. The pilot places were available in a variety of early years settings e.g. nurseries, play groups and with childminders, but all were required to operate the Birth to Three Matters curriculum.